Application of Balanced Fertilization to Rice Farmers in Darat Sawah Ulu Village, Seginim District, South Bengkulu Regency - Putra, Afri Chandra; Sujono, Sujono; Nurlaela, Siti (Tropical Plantation Journal, 2025)
Soil fertility depletion due to chemical fertilizers is one of the causes of low productivity of rice plants. This study aims to determine the application of balanced fertilization to rice farmers in Darat Sawah Ulu Village, Seginim District, South Bengkulu Regency, and to design an empowerment design that supports the implementation of a balanced fertilization system. This research was carried out from January to June 2024 in Darat Sawah Ulu Village, Seginim District, Bengkulu Province. This study uses a quantitative descriptive approach with a survey method using a questionnaire as an instrument used in the research. The sample used was 40 respondents. The level of balanced fertilization application in Darat Sawah Ulu Village, Seginim District, South Bengkulu Regency is in the high category with the average percentage of 5 correct applications is 77.214%.  Agricultural extension workers need to assist to maintain the sustainability of implementing this highly balanced fertilizer with appropriate programs.